2010
DOI: 10.1038/jp.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Validity of neonatal jaundice evaluation by primary health-care workers and physicians in Karachi, Pakistan

Abstract: Objective: The purpose of this study was to validate primary health-care workers' and physicians' visual assessment of neonatal hyperbilirubinemia in Karachi, Pakistan.Study Design: We compared primary health-care workers' and physicians' clinical identification of jaundice in infants <60 days old.Result: Primary health-care workers identified 1-to 20-day-old neonates with hyperbilirubinemia X15 mg per 100 ml (260 mmol l À1 ) with 83.3% sensitivity and 50.5% specificity; neonates aged 1 to 6 days were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…Mothers and other care-givers should be encouraged to look for jaundice by blanching the skin (on the nose in particular), looking at the gums and examining the eyes [ 4 ]. The use of Kramer’s chart (see Additional file 3 : Figure S1) especially in primary care settings remains valuable despite its limitation in correlating with the severity of jaundice [ 37 , 38 ]. So also is blanching of the gums possibly with an icterometer, particularly in dark-skinned babies [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Mothers and other care-givers should be encouraged to look for jaundice by blanching the skin (on the nose in particular), looking at the gums and examining the eyes [ 4 ]. The use of Kramer’s chart (see Additional file 3 : Figure S1) especially in primary care settings remains valuable despite its limitation in correlating with the severity of jaundice [ 37 , 38 ]. So also is blanching of the gums possibly with an icterometer, particularly in dark-skinned babies [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…In developing countries lacking routine screening protocols, significant jaundice is often missed. 4 In north Vietnam, national screening protocols and management guidelines are lacking for newborn jaundice. A recent regional study of tertiary referrals for jaundice in northern Vietnam showed that 22% of infants had serum bilirubin levels requiring exchange transfusion, and 28% demonstrated signs of acute bilirubin encephalopathy on admission to hospital.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Mothers were taught how to give a jaundice score by blanching the skin with digital pressure to assess the underlying skin color in sufficient ambient light. Mothers were asked to score and record the level of jaundice once daily for six consecutive days as follows: none (0), face (1), chest (2), legs and/or arms (3), or palms of hands and/or feet (4).…”
Section: Training Modulementioning
confidence: 99%
“…Controversial findings on reliability of this technique for detecting NJ have been reported worldwide. Studies conducted in Pakistan (2010) and Indonesia (2017) reported that Kramer’s method is reliable in detection of NJ and darker skin color is not a matter of concern [ 7 , 8 ]. However, a study conducted in United State of America (USA) reported that Kramer’s method alone is not reliable in detecting NJ especially in darkly pigmented neonates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%